Temperature dependence of the yield strength of aluminum thin films: Multiscale modeling approach. (1st April 2017) - Davoudi, Kamyar
Abstract: Modeling deformation at elevated temperatures using discrete dislocation dynamics (DDD) is a recent area of high interest. However, the literature dedicated to this subject fails to address the variations of DDD parameters with temperature. This study aims to investigate the effect of temperature on the yield strength of aluminum thin films in two-dimensional DDD simulations. To this end, the temperature dependence of DDD parameters has been studied using molecular dynamics, three-dimensional DDD simulations, and the existing experimental results. Based on these calculations, we observed 18% decrease in the yield strength when temperature was increased from 100 K to 600 K. Graphical abstract: